Femtosecond Laser Assisted Deep Anterior Lamellar Keratoplasty Outcomes and Healing Patterns Compared to Manual Technique. (18th October 2015) - Alio, Jorge L.; Abdelghany, Ahmed A.; Barraquer, Rafael; Hammouda, Laila M.; Sabry, Ahmed M.
Abstract : The purpose of the study is to report the visual, refractive, and wound healing pattern outcomes of femtosecond assisted deep anterior lamellar keratoplasty (DALK) compared to the conventional manual technique. DALK was performed on 50 eyes of 47 advanced keratoconus patients. The patients were divided into two groups, 25 eyes each, depending on whether femtosecond assisted or manual DALK technique was performed for the side cut of the procedure only. Patients were followed up at 1 month, 6 months, and 1 year for visual acuity, clinical refraction, corneal cylinder, date of suture removal, and side cut corneal healing pattern according to new grading classification of the side cut scar (Grade 0 = transparent scar, 1 = faint healing opacity, 2 = evident healing opacity, 3 = significant opacity with some cosmetic imbalance, and 4 = highly significant opacity with very significant cosmetic imbalance). Outcomes are reported at one year. In conclusion, femtosecond assisted and manual DALK show comparable visual and refractive outcomes but femtosecond assisted DALK shows more evident corneal wound healing patterns at the side cut. This observation may indicate that an activated cornea wound healing might allow earlier suture removal when femtosecond technology is used to perform the side cut for DALK.